AVALIAÇÃO DO EFEITO ANTIMICROBIANO E ANTIBIOFILME DE UM INIBIDOR DE PEPTIDASE DE Inga cylindrica - ANA PAULA RAMOS PEREIRA (2022)
The discovery of antibiotics revolutionized infection control. However, the history of antibiotics and the development of microbial resistance go hand in hand. Thus, the search for new antimicrobials began. In the last decades, antimicrobials from plant species have been highlighted. Plant cellular enzyme inhibitors can destabilize pathogens through membrane and/or wall damage and changes in cell permeability. This study aimed to evaluate the antimicrobial potential of the trypsin inhibitor from Inga cylindrica seeds, investigate its mechanism of action against pathogenic yeasts, as well as its toxicity in Galleria mellonella. After the minimum inhibitory concentration MIC), minimum concentration (CFM) and antibiofilm activity were isolated, fungicidal. The synergistic effects of ICTI in association with anthericin B and ICTI toxicity against G. mellonella were also analyzed. ICTI is a protein consisting of a single polypeptide chain of approximately 20 kDa. ICTI inhibitory activity was trip-specific. The ICTI does not have bactericidal activity, but has fungicidal action. The ICTI showed a MIC of 32.11 μM for C. albicans 90028 and C. gattii AFLP4. The action of ICTI with amphotericin B showed a synergistic effect. The ICTI at MIC inhibited the biofilm formation of C. albicans 90028 and C. gattii AFLP4, by 38.5% and 21.5%, respectively. The ICTI at MIC also promotes the eradication of mature biofilm forms of C. albicans 90028 and C. gattii AFLP4, 37.2% and 22.1%, respectively. Based on the results obtained, we suggest that the antifungal activity of ICTI involves binding to ergosterol present in the fungal cell membrane. This specific action is also observed in polyene antifungals such as amphotericin B. Given the ability of ICTI to bind to ergosterol, membrane damage occurring intracellularly, promoting work extravasation, as demonstrated by the work results. Finally, ICTI was not toxic when administered in the G. mellonella model, or that it supports future trials in other animal models.